Liver and kidney histopathological test of mice received Pauh Kijang (Irvingia malayana Oliv ex A. Benn) extract - Praptiwi .; Dewi Ratih Agungpriyono; Esti Rahayu (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
The background of this study was to determine the safety of pauh kijang extract which is orally given to mice while the aim of the study was to evaluate the liver and kidney histopathological changes after receiving various dose of the extract mango (Irvingia malayana Oliv. Exe Benth.) ethanol extract. There were five group of treatments in this study : mice received extract with the concentration of (I) 1000mg /kg BW, (II)100 mg/kg BW, (III) 10 mg/kg BW, (IV) 1 mg/kg BW, and (V) received carboxy methyl cellulose-sodium (CMC-Na) as negative control. Each treatment consisted of five mice. After seven days of treatment, mice were sacrified. The liver and kidney were sampled and processed to prepare histopathology slides. The histopathology parameters were examined by counting the degeneration and necrotic cells of hepatocytes and renal epithelial tubule. The lesion of glomerulus such as atrophy and protein sedimentation were also observed. The result also showed that extract concentration of > 10 mg/kg BW result in damaging liver cells significantly, while kidney cell damage occurred significantly in the exposure of extract > 1 mg/kg BW.Key words : Irvingia malayana, liver, kidney